Executive function and adult homelessness, true impairment or frontal lobology? - Pluck, Graham (Frontiers in Human Neuroscience, 2024)
Homelessness is associated with multiple risk factors for neurocognitive impairment. Past research with people experiencing homelessness has described “frontal lobe” dysfunction including behavioral disorders and executive cognitive impairments. In the current study, 72 adults experiencing homelessness were assessed with a standardized assessment of executive function, and interviewed regarding neurological and psychiatric history. When compared to a control sample of 25 never-homeless participants, and controlling for level of education, there was little evidence for executive dysfunction in the sample of people experiencing homelessness. Levels of substance abuse, past head injury, and post-traumatic stress disorder were notably high. However, there were no statistically significant associations between cognitive task performance and clinical or substance abuse variables. Gambling was surprisingly infrequent, but risk-taking behavior among intravenous drug users was common. Though in neither case was it linked to executive function. Overall, there was little evidence for executive impairment in this sample of people experiencing homelessness. I suggest that past research has often used inappropriate criteria for “normal” performance, particularly comparing people experiencing homelessness to control data of relatively high education level. This has led to elements of “frontal lobology,” that is, clinical neuroscience research that tends to overly link non-typical or pathological behavior to frontal lobe impairment. When appropriate comparisons are made, controlling for education level, as in this study, associations between executive function impairments and adult homelessness may be weaker than previously reported.